1991
DOI: 10.1063/1.459891
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of the liquid–vapor interface of water

Abstract: We report the results of molecular dynamics simulations of the liquid–vapor interface of water. Two different water–water interactions were studied. The density profile of the interfacial transition region between liquid and vapor is monotone with a 10%–90% width of 3.45 Å, in good agreement with the value determined from x-ray reflectance measurements, namely 3.30 Å. The water molecules in the interface tend to lie with the HOH bisector in the plane of the surface and one OH bond pointing out of the surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
124
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 8 publications
13
124
1
Order By: Relevance
“…The maximum probability is at an angle of 120°with the outward surface normal, which qualitatively agrees with the experimental second-harmonic generation results. 19 Most of the ''classical'' simulations studies also agree with our result, [21][22][23]25 although two studies reported a water dipole orientation parallel to the surface. 20,24 The intramolecular O-H bond orientation can be described by an angle variable between the bond and the surface normal in analogy to the dipole moment orientation angle .…”
Section: Molecular Dynamics Simulation Of Water-vapor Interfacesupporting
confidence: 79%
See 2 more Smart Citations
“…The maximum probability is at an angle of 120°with the outward surface normal, which qualitatively agrees with the experimental second-harmonic generation results. 19 Most of the ''classical'' simulations studies also agree with our result, [21][22][23]25 although two studies reported a water dipole orientation parallel to the surface. 20,24 The intramolecular O-H bond orientation can be described by an angle variable between the bond and the surface normal in analogy to the dipole moment orientation angle .…”
Section: Molecular Dynamics Simulation Of Water-vapor Interfacesupporting
confidence: 79%
“…2, which shows the computed xy (Nϭ2) and z (Nϭ1) components of the MSD of the O atoms, only ''cage movement'' effects are observed, resulting in the small slope of the curve at longer times. This picture contradicts the findings in earlier ͑classical͒ MD simulations, 22,25 where an increase of the self-diffusion coefficient in the surface transition zone compared to the bulk region was reported. These simulations were performed using much bigger systems containing 350 or more water molecules.…”
Section: Molecular Dynamics Simulation Of Water-vapor Interfacecontrasting
confidence: 57%
See 1 more Smart Citation
“…12,38,39 Besides SHG and SFG-VS experimental studies, 33,40 Structure and dynamics of water molecules at the air/water interface have also been intensively discussed with theoretical simulations. 5,6,7,8,9,10,11,12,13 Even though with so much efforts and progresses both by experimentalists and theoreticians, our detailed understanding of air/water interface is still limited. Just as indicated by B. C. Garrett recently, 41 '...(direct) experiments are difficult to perform because the liquid interface is disordered, dynamic, and small (typically only a few molecules wide) relative to the bulk'.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4 Among them, air/water interface has been intensively investigated theoretically or experimentally over the last decades. Spectroscopy, molecular structure and dynamics at air/water interface is studied with theoretical analysis such as ab initio calculation or molecular dynamics simulation, 5,6,7,8,9,10,11,12,13 or experimental techniques such as X-ray reflection, 14,15 Stimulated Raman Scattering (SRS), 16 Near-edge X-Ray Adsorption Fine Structure (NEXAFS), 17 Second Harmonic Generation (SHG), 18,19 as well as Sum Frequency Generation, etc. 20,21,22,23,24,25,26,27,28 Among these experimental techniques, Second Harmonic Generation and Sum Frequency Generation are the most important methods for molecular interface studies because of their surface sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%